The Old African - Lester, Julius; Pinkney, Jerry (New York : Dial Books, 2005)
An elderly slave uses the power of his mind to ease the suffering of his fellow slaves and eventually lead them back to Africa. Based on an actual incident from black history.
Keywords: Slavery -- Fiction; African Americans -- Fiction; Extrasensory perception -- Fiction; Telepathy -- Fiction